Hubungan Adversity Quotient Dan Stres Pada Siswa Kelas Xii Yang Akan Mengikuti Ujian Nasiona Di SMAN 1 Padang - Andhika Anggawira (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2019)
The study objective was to determine correlation between adversity quotient and stress of 12th grade in senior high school 1 Padang that who will be held on final examination for their graduation. This research used survey method and the analaysis used correlation techniques. Sample Size of 158 obtained by purposive sampling technique. The instrument used was aquestionaire to measure stress by HSCL-25 and adversity quetion by likert scale’s Rahmawati (2007). The result shown 65% students has indicated stress, and 71 % student has middle range on adversity quotient. Result of the hypothesist namely there is negative correlation between adversity quotient and stres but they don’t have enough significant’s value.